The life-course association of birth-weight genes with self-rated health. (3rd July 2019) - Tong, Guangyu; Guo, Guang
ABSTRACT: This study examines the impact of genes associated with normal-range birth weight (2500–4500 grams) on self-rated health in mid-to-late life course. Fifty-eight previously identified genetic variants that explain the variation in the normal-range birth weight were used to construct a genetic measure of birth weight for the non-Hispanic white sample from the Health and Retirement Study. Our results show that the genetic tendency toward higher birth weight predicts better self-rated health in mid-to-late life course net of various demographic, socioeconomic, and health behavioral factors. We also examine the heterogeneous effects of birth-weight genes across birth cohorts and age groups. Moreover, to clarify the paradox that higher birth weight can predict both better self-rated health and higher BMI, we show the positive association between birth weight genes and BMI can only hold within the normal-range BMI (18 ≤ BMI < 30). Overall, these findings suggest the genetic factors underlying the normal-range birth weight can have life-courseimpacts on health.